Ashh&Annas sales promotion; Does it affect brand equity? / Siti Norsaleha Mastor - Mastor, Siti Norsaleha (2017)
The competition between retailers and companies are getting fierce day by day. As a result of this situation, the retailers carried out sales promotion in order to induce the sales volume and at the same time to attract the customers to buy their products. Sales promotion is known as a good act to invite the customers to buy the product, either at the physical store or online store, but the frequent use of the sales promotion itself, might give negative effect to the brand, especially in long term period. One of the effects that the retailers might face is devalue in brand equity, as the retailer might use sales promotion too often; until the brand itself lost its exclusivity and uniqueness that once becomes the centre of attention of the customers. In the competitive environment of retail industry, the brands that have high brand equity is actually the brand that have the most advantages, as the customers nowadays prefer the brand that is well accepted and widely known by the mass media. Hence, it is one of the Ashh&Annas objectives to be the brand that have high brand equity, but the act of carrying out too many sales promotions is absolute contra from the objectives that they try to achieve. Thus, this study is to determine, whether the sales promotion carried out by Ashh&Annas actually influence the brand equity of the brand or not. The result of this study obtained through the survey using the questionnaire with 100 respondents, which all of them is the customers of Ashh&Annas. There are 4 variables used in this study, which are brand loyalty, brand quality, brand association and brand awareness. The result of this study also expected to help the retailers to better understand the long term effect of sales promotion, if it's been used recklessly.